Obtenção e caracterização de amido de mandioca (Manihot esculenta Crantz) modificado com ácido tartárico - Viell, Franciele Leila Giopato (2015)
The chemical modification of native starch cause structural changes in the polymer molecule affecting their physic-chemical properties which make them suitable for various industrial uses. Tartaric acid is an organic dicarboxylic acid which can chemically modify the starch structure and its use is allowed in foods. In this study, the tapioca starch was modified with tartaric acid and the effect of acid concentration (4.5 to 8.0 g.100g-1) and the reaction pH (5.0 to 8.0) on the properties starch were evaluated using a 22 face-centered central composite design. The physico-chemical properties, functional, and pasting properties were determined. The infrared spectra Fourier transform (FT-IR) and the morphology of granules by scanning electron microscopy (SEM) was also evaluated. The modification reduced the intrinsic viscosity and the amylose contents with the increase of the acid concentration and decrease of pH. At pH 5.0, there was a higher percentage of mono tartarate ester and higher swelling and solubility of starches were observed. At pH 6.5 and 8.0, the modification caused a reduction in the swelling and solubility, increased resistance to freeze-thaw and improvement in the pasting properties (increased thermal and mechanical resistance). FT-IR confirmed qualitatively the esterification of starch by the appearance of bands attached to ester groups in the tests performed at pH 5.0. The modification did not cause obvious changes in the external morphology of the starch granules as observed by MEV. It was possible to conclude that the effect of acid concentration on the properties of the starch was less than the effect of pH where lower pH values favor the esterification of starch and higher pH values favor the crosslinked.